2012
DOI: 10.29252/jmj.10.1.7
|View full text |Cite
|
Sign up to set email alerts
|

The effects of parental bonding on depression and self esteem in adolescence

Abstract: Introduction: Depression and low self-esteem are the most important psychological disorders common among adolescents. But few studies have investigated the association between parental bonding patterns and depression and low self esteem in adolescents. The aim of this study was to detect the effects of parental bonding on depression and self esteem during adolescence in Bushehr in 2010. Material and Methods: In this cross-sectional study, a total of 482 adolescents (246 females and 236 males) in the first grad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 15 publications
0
6
0
2
Order By: Relevance
“…On one side, the college students need autonomy and independence to separate with their parents; on the other side, they still need the close emotional bonding with their parents to feel safety when they explore their inner and external world ( 21 ). Several studies have shown that there was a significant correlation between the development of adolescents’ self-esteem and parental bonding style, and the researchers have found that insufficient care and excessive control by parents lead to depressive symptoms and low self-esteem ( 22 – 24 ). Other findings suggest that high self-esteem and self achievement of the adolescents positively associated with high levels of intimacy and emotional expression in the family ( 25 ); the closeness of family members and the expectations of parents will influence the college freshmen’s self-esteem and self-concept ( 26 ).…”
Section: Introductionmentioning
confidence: 99%
“…On one side, the college students need autonomy and independence to separate with their parents; on the other side, they still need the close emotional bonding with their parents to feel safety when they explore their inner and external world ( 21 ). Several studies have shown that there was a significant correlation between the development of adolescents’ self-esteem and parental bonding style, and the researchers have found that insufficient care and excessive control by parents lead to depressive symptoms and low self-esteem ( 22 – 24 ). Other findings suggest that high self-esteem and self achievement of the adolescents positively associated with high levels of intimacy and emotional expression in the family ( 25 ); the closeness of family members and the expectations of parents will influence the college freshmen’s self-esteem and self-concept ( 26 ).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, researchers investigated the healthy dormitory students of a university in Iran. On the contrary, the results of another study in Iran revealed that depression and lack of self-con dence rates in children signi cantly increased in parenting styles in which parents exaggerated in caring for or controlling their children [19].…”
Section: Introductionmentioning
confidence: 93%
“…Based on the score of parental bonding tool in patients with schizophrenia and bipolar disorder in a study by Gomez et al [16], using the sample size formula (N = z1-α/2 2 S2/d2 (and assuming that α = 0.05 and d = 0.3S, we speci ed the sample size of different disorders as follows; at least 44 patients with schizophrenia and a minimum of 43 patients with bipolar. According to the parental bonding scores of depressed patients in a study by Bahreini et al [19], the sample size for patients with depression was estimated to be at least 43. In performing the pairwise comparison between the parental bonding styles of patients with schizophrenia, bipolar disorder, and depression, the sample size obtained through sample size formula for pairwise comparison, ( N=2( z1−α/2 + z1−β ) 2 S2/d2 , S 2 = (s 1 2 + s 2 2 ) /2, d 2 = (µ 1 -µ 2 ) 2 ), was less than that calculated for each group when α = 0.05 and study power = 80%; therefore, the minimum sample size was assumed to be equal to the minimum sample size of each group.…”
Section: Design and Participantsmentioning
confidence: 99%
“…In this study, researchers investigated the healthy dormitory students of a university in Iran. On the contrary, the results of another study in Iran revealed that depression and lack of self-confidence rates in children significantly increased in parenting styles in which parents exaggerated in caring for or controlling their children [ 20 ].…”
Section: Introductionmentioning
confidence: 99%